PENGARUH PENDEKATAN MODELLING DAN PENGETAHUAN AWAL TERHADAP HASIL BELAJAR (Studi Eksperimen pada Pelajaran Bahasa Inggris kelas V SD Cendana Pekanbaru) - Jakfar, M; Jasrial, Jasrial; Mukhaiyar, Mukhaiyar (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2011)
The learning process should be presented more varied and ivonative. Modeling approach is one alternative that is used. This study aims to reveal Effect of Initial modeling approach and ability to learn English Results, whereas the problems presented in this study are: (1) whether there are differences in student learning outcomes of the modeling approach to student learning in the conventional?, (2) whether students who have prior knowledge modeling approach to obtain high with higher learning outcomes of the students' learning in the conventional?, (3) whether the student has the ability to lower the initial modelling approach to obtain higher learning outcomes of the students to learn the conventional?, (4) whether there is an interaction between the modeling approach and the ability early on student learning outcomes?.This research is a quasi experimental design with a design factorial by 2 x 2. The research was conducted in Pekanbaru Cendana Junior High School even semester academic year 2013/2014. Samples were taken with a random sampling technique porposive. Data were collected through the end of the test. Data were analyzed by t test and analysis of variance.The results of data analysis showed that the results of student learning with higher modeling approach of the learning outcomes of students who learned in the conventional. The results of students learning English by high initial ability taught modeling approach is higher than conventional learning. The results of students learning English is based on a low initial ability taught modeling approach is higher than conventional learning. There is no interaction modeling approach and ability early on student learning outcomes.